INFLAMMATORY BOWEL DISEASE: OUTPATIENT TREATMENT PROFILE - SANTOS,Rachael Miranda dos (2017)
ABSTRACT BACKGROUND Crohn’s disease and ulcerative colitis are the two major forms of inflammatory bowel disease. The incidence and prevalence of both conditions have increased and are progressively increasing. These diseases are frequently recurrent and clinically highly severe. In Brazil, the lack of epidemiological data related to such diseases has left these patients in a vulnerable state and contributed to increased morbidity. OBJECTIVE To describe the profiles of patients with inflammatory bowel disease treated in an outpatient service in Brazil. METHODS This descriptive, exploratory, and retrospective documentary study with a quantitative approach was performed in an outpatient treatment service for inflammatory bowel disease, at a university polyclinic located in Rio de Janeiro, Brazil, from May to July 2016. The study included 556 patients and was approved by the research ethics committee of the institution (CAAE no. 55179316.6.0000.5259/2016). RESULTS The data showed a high prevalence of inflammatory bowel disease in white female patients. Crohn’s disease was diagnosed in more patients than was ulcerative colitis; the ileocolon was the most commonly affected location in patients with Crohn’s disease. The stenotic phenotype was prevalent in patients with Crohn’s disease. CONCLUSION The prevalence of the stenotic phenotype in Crohn’s disease in relation to others demonstrates the need for further investigations in this field of study in Brazil. In conclusion, the data showed that the epidemiologic profile of the study population is similar to that published in the national and international literature.